G202(P) Outcomes of extremely low birth weight infants – the effect of being small for gestational age. (12th March 2018) - Charles, E; Harris, C; Hickey, A; Greenough, A
Abstract : Aims: Prematurely-born infants who are small for gestational age (SGA) have worse outcomes than those who are born appropriate for gestational age (AGA). 1, 2 There has, however, been little focus on SGA infants born at extremely low birth weights (BW <750 g). Methods: A retrospective study was undertaken of all babies BW <750 gm born between 2012 and 2016. Centiles and z-scores were calculated using the UK WHO preterm reference ranges (British 1990 reference data, reanalysed 2009). The infants were divided into SGA (<10 th centile) and AGA (10th – 90th centile) groups. Multiple logistic regression analysis was performed to adjust for gestational age to relate individual outcome variables to SGA. Results: Eighty-four infants were included, 35 (42%) were SGA. The SGA infants were more mature (median gestational age 26.9 versus 24.3 weeks, p<0.001), had a lower birth weight centile (median 1 versus 26, p<0.001); their mothers were more likely to have received antenatal steroids (94% versus 78%, p=0.022), had hypertension (49% versus 8%, p<0.001) and be delivered by caesarean section (69% versus 8%, p<0.001). Neither the mortality (31% versus 32%) nor the incidence of NEC (17% versus 16%) differed significantly between the two groups, but more of the SGA developed severe BPD (p=0.025). The SGA infants achieved full enteral feeds at an older postnatal age (median 54 versus 48 days, p=0.019). The length of stay was similar in the two groups (127 versus 131 days), but the weight z score at discharge was lower in the SGA group (−3.6 versus −1.7) (p=0.001). Indeed, there was no significant difference in the change in z score from birth between the two groups (median −1.53 versus −1.07, p=0.306). Conclusions: Amongst infants with a BW <750 gm, SGA compared to AGA suffered greater morbidity, but not mortality. These data are important for counselling parents as, in this population, any advantage of later gestation may be negated by being SGA. References: . Peacok JL, et al. Pediatr Res2013;73:457–63. . Tsai L-Y, et al. Pediatr Neonatol2015;56:101–7.